PENATALAKSANAAN FISIOTERAPI PADA KONDISI ASMA BRONCHIALE DENGAN MODALITAS INFRA MERAH, CHEST FISIOTERAPI DAN LATIHAN PROGRESSIVE MUSCLE RELAXATION DI BBKPM SURAKARTA - Rizza Mustafa; Ade Irma Nahdliyyah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
Bronchial asthma is a disorder characterized by continuous broncus hypersecretion and empysema, in which loss of lung supporting tissue causes severe respiratory tract narrowing that is especially noticeable when breathing out. In asthma, there are 3 (three) types of concurrent processes, namely inflammation (inflammation) in the respiratory tract, narrowing of the airway (bronkokonstriksi), excessive exposure of mucus / mucus fluid resulting from the three processes in the asthma, the asthma patients may experience difficulty breathing or tightness accompanied by coughing and wheezing.Management of physiotherapy in the condition of Bronchial asthma can be administered by using the modality Infrared, Chest Physiotherapy and Exercise Progressive Muscle Relaxation (PMR). The research method used by the writer is using case study. after physiotherapy action five times, the result of decreased shortness of breath was measured by borg scale from T1 = 4 to T5 = 0, the decrease of respiratory muscle spasm was measured by palpation from T1 = 1 to T5 = 0, presence sputum production decline is measured by auscultation and the number of sputum that comes out from the results T1 = wheezing (++) Crackles (++) Vout = 30 ml to T1 = wheezing (-) Crackles (+) Vout = 0 ml, the increasing expansion of the thoracic cage metline from results measured using T1 = 1 cm difference in axillary axis, ICS 4-5 and P. xyphoideus into T5 = 1.5 cm difference in axillary axis, ICS 4-5 and P. xyphoideus and an increase in functional activity was measured using the 6MWT From the result of T1 = 357.8 meters to T5 = 440 meters.From the results already obtained, it can be concluded with physiotherapy treatment on the condition of Bronchial asthma by using Infrared, Chest Physiotherapy and Exercise Progressive Muscle Relaxation (PMR) can help reduce problems arising on the condition of Bronchial asthma.